Depression and its association with menstrual disturbance among female university students: a cross-sectional study - Md Sabiruzzaman; Md Golam Hossain; Shangida Khatun Eva; Saqib Salah Aufi; Abu Sayed Md Al Mamun; Md Abdul Wadood (BMJ Publishing Group, 2024)
Background Depression and menstrual disturbance are common issues among female university students worldwide. Various studies in different countries have revealed a potential connection between depression and menstrual disturbance. However, no research specifically focusing on this relationship has been conducted with the Bangladeshi population. Thus, we aimed to investigate the prevalence of depression and its impact on menstrual disturbance among female university students in Bangladesh.Methods Data were collected from 470 female students of the University of Rajshahi in Bangladesh between September and November 2022. A multistage stratified random sampling method was employed to select a sample from the population. Depression severity was assessed using the nine-item Patient Health Questionnaire, categorising it as normal, depressive symptoms and probable depression. Two menstrual disturbances, irregular and painful menstruation, were considered. The factors associated with depression were examined using an ordinal logistic regression model.Results The findings indicated that 45.5% of female university students exhibited depressive symptoms, while 30.9% have probable depression. Additionally, 71% experienced menstrual pain and 17.7% reported irregular menstruation. Factors significantly associated with probable depression (p<0.05) included being underweight; paternal occupation other than a farmer, having a job or being in business; low-income and middle-income family; and having a chronic disease. Furthermore, students with depressive symptoms and probable depression were found to be at higher risk of experiencing menstrual disturbances, particularly painful and irregular menstruation. Specifically, those with depressive symptoms and probable depression were more likely to report painful menstruation.Conclusion In this study, it was noted that a notable proportion of female students were experiencing probable depression, which was found to have an association with menstrual disturbance. It is advisable that healthcare providers and university authorities prioritise the mental and reproductive health of female students for their holistic well-being.